2016
DOI: 10.1149/2.0141612jss
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Integrated MEMS Enabled by AAO Process Technologies

Abstract: An alternative approach to fabricate specialty MEMS devices by heterogeneous integration of dissimilar materials such as PCB substrates and neodymium magnets with anodic aluminum oxide (AAO) templates was demonstrated. The importance of the use of copper metal as an intermediate layer for wet chemical etching of AAO templates in order to release MEMS devices was presented. The assembling of dissimilar materials before the final wet chemical etch and release was introduced which is not possible with standard ME… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Researches have been published [16][17][18][19][20][21] previously to fabricate and characterize porous anodic aluminum oxide (AAO) interposer using the same concept of growing metallic nanowires in AAO as interconnects. Previously, however, fabrication works has been done to create through AAO interconnects taking advantage of the anisotropic structural and etch properties 22 of vertically self-aligned nanopores. [23][24][25] Reasons behind considering AAO as a potential substrate for interconnects and integrated passive devices (IPDs) are AAO's good electrical property, mechanical toughness, unique nanoporous structures, easiness in fabrication and customization, and so on.…”
mentioning
confidence: 99%
“…Researches have been published [16][17][18][19][20][21] previously to fabricate and characterize porous anodic aluminum oxide (AAO) interposer using the same concept of growing metallic nanowires in AAO as interconnects. Previously, however, fabrication works has been done to create through AAO interconnects taking advantage of the anisotropic structural and etch properties 22 of vertically self-aligned nanopores. [23][24][25] Reasons behind considering AAO as a potential substrate for interconnects and integrated passive devices (IPDs) are AAO's good electrical property, mechanical toughness, unique nanoporous structures, easiness in fabrication and customization, and so on.…”
mentioning
confidence: 99%
“…One promising material in particular, anodized aluminum oxide (AAO), has been explored for potential use in microelectronic applications. [1][2][3] While AAO material shows promise as a microelectronic material, a significant limitation is in metalizing the surface at low cost.…”
mentioning
confidence: 99%
“…Furthermore, it has been found that AAO films also have high anisotropy for chemical wet etching due to their vertical pore structures. 1,11,12 Thus, microstructures can be fabricated from AAO films by combining photolithography and wet chemical etching without the need for high-cost deep etch processes to form high aspect ratio structures with vertical sidewalls. These unique properz E-mail: melonmj0219@gmail.com ties have attracted research and work in porous AAO films for applications in nanowire fabrication, biomedical devices, [13][14][15] microelectromechanical systems (MEMs), microelectronics, interposers, and RF substrates.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Research and development works have been done in templating AAO for high aspect ratio anisotropic nanowire fabrication and applications, [9][10][11] low cost metallic nanotip arrays fabrication, 12 and nano-patterning mask on Si wafer. 13 This work, instead, took advantage of the distinct anisotropic etching characteristic from nanoporous characteristic of AAO [14][15][16] to create structures with vertical sidewall was carried out to fabricate through via. Interconnects in AAO were completed after void-free bottom-up Cu electroplating through AAO vias.…”
mentioning
confidence: 99%